Acute Psychosis Triggered by Ovarian Teratoma: The Underdiagnosed yet Treatable Case of Anti-NMDA Receptor Encephalitis - Keller, Shikma; Roitman, Pablo; Ben-Hur, Tamir; Neuman, Tzahi; Bonne, Omer; Lotan, Amit (Highlights on Medicine and Medical Research Vol. 6, 2021)
Anti-NMDA receptor (NMDAR) encephalitis is a recently identified autoimmune disorder with prominent psychiatric symptoms. Patients usually present with acute behavioral change, psychosis, catatonic symptoms, memory deficits, seizures, dyskinesias and autonomic instability. In female patients an ovarian teratoma is often identified. We describe a 32-year-old woman who presented with acute psychosis. Shortly after admission, she developed generalized seizures and deteriorated into a catatonic state. Although ancillary tests including MRI, electroencephalogram and cerebrospinal fluid (CSF) analysis were unremarkable, the presentation of acute psychosis in combination with recurrent seizures and a relentless course suggested autoimmune encephalitis. The patient underwent pelvic ultrasound which disclosed an ovarian tumor, leading to an urgent cystectomy with pathological confirmation of a mature cystic ovarian teratoma. Plasmapheresis was then initiated, yielding partial response over the next two weeks. Following the detection of high titers of anti-NMDAR antibodies in the CSF, the patient ultimately received second line immunosuppressive treatment with rituximab. Over several months of cognitive rehabilitation, a profound improvement was eventually noted, although minor anterograde memory deficits remained. In this report we call attention to the inclusion of anti-NMDAR encephalitis in the differential diagnosis of acute psychosis. The inclusion of this disorder in the differential diagnosis is critical, as prompt initiation of immunotherapy and tumor removal, if appropriate, could dramatically affect outcome.